The Influence Of Interest Rates, Inflation And Exchange Rates On Banking Profitability In Indonesia - Andi Muhammad Adriansyah Sam; Basri Bado; Sri Astuty; Irwandi Irwandi; Regina Regina (International Journal of Economic Research and Financial Accounting, 2025)
This research aims to determine the influence of monetary and macroeconomic variables on the profitability of banking in Indonesia. The independent variables used are the Interest Rate (BI-Rate), Inflation, Exchange Rate, and for the dependent variable, the Return On Assets (ROA) of banks in Indonesia for the period 2009-2023. The method that will be used in this research is Panel Data with analysis using the Eviews 12 application. The research results show that interest rates do not affect the profitability of state-owned banks or private banks. The inflation variable has different effects on the profitability of each bank, namely it affects state-owned banks (BUMN) but does not affect private banks. Similarly, the Exchange Rate has different effects on each bank's profitability, namely, it does not affect State-Owned Enterprises (BUMN) banks and does affect Private banks